2011
DOI: 10.1038/nn.2780
|View full text |Cite
|
Sign up to set email alerts
|

HDAC-mediated deacetylation of NF-κB is critical for Schwann cell myelination

Abstract: Schwann cell myelination is tightly regulated by timely expression of key transcriptional regulators that respond to specific environmental cues, yet molecular mechanisms underlying such a process are poorly understood. Here, we report that HDAC1/2-regulated acetylation state of NF-κB is critical in orchestrating the myelination program. Mice lacking HDAC1/2 exhibit severe dysmyelination with Schwann cell development arrested at the immature stage. We find that NF-κB p65 becomes heavily acetylated in HDAC1/2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
151
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(162 citation statements)
references
References 23 publications
11
151
0
Order By: Relevance
“…It is known that activation of the angiotensin system induces Smad3 phosphorylation and oxidative stress [29][30][31] whereas HDAC interacts with the NFkB pathway. 32 Our findings are consistent with our computational predictions. These results support that SAHA and benazepril probably affect distinct pathways in the diseased kidney.…”
Section: Pathway Validation In Kidneys Of Mice Treated With Benazeprisupporting
confidence: 91%
“…It is known that activation of the angiotensin system induces Smad3 phosphorylation and oxidative stress [29][30][31] whereas HDAC interacts with the NFkB pathway. 32 Our findings are consistent with our computational predictions. These results support that SAHA and benazepril probably affect distinct pathways in the diseased kidney.…”
Section: Pathway Validation In Kidneys Of Mice Treated With Benazeprisupporting
confidence: 91%
“…The lysate was incubated with HA binding resin at 4°C for 2 hours. At that point, the bait was eluted 3 times using excess HA peptide (1 mg/ml in 20 mM Tris-HCl [pH 7.4], 100 mM Moreover, NF-κB plays an important role in neuronal function and learning processes (41,42) and is similarly important for myelination and Schwann cell function (43). Therefore, the alterations in the NF-κB pathway seen in these patients may contribute to their neurologic phenotype.…”
Section: Figurementioning
confidence: 99%
“…There is general agreement that histone deacetylases play an essential function in regulating differentiation of neural precursor cells to oligodendrocytes in the developing brain in rodents (MarinHusstege et al, 2002;Shen et al, 2005;Ye et al, 2009;Chen et al, 2011;Jacob et al, 2011). It was reported that genetic ablation of HDAC1 and HDAC2 in the mouse blocks oligodendrocyte differentiation by activation of Wnt/beta catenin signaling pathway.…”
Section: The Involvement Of Hdac1 and Hdac2 In Neurogenesismentioning
confidence: 99%